2018
DOI: 10.1073/pnas.1802223115
|View full text |Cite
|
Sign up to set email alerts
|

Noncatalytic chalcone isomerase-fold proteins in Humulus lupulus are auxiliary components in prenylated flavonoid biosynthesis

Abstract: SignificanceHere, we identify two noncatalytic chalcone isomerase-fold proteins, which are critical for high-efficiency prenylchalcone production in Humulus lupulus. Our results provide insights into their evolutionary development from the ancestral noncatalytic fatty acid-binding chalcone isomerase-fold proteins to specialized auxiliary proteins supporting flavonoid biosynthesis in plants, and open up the possibility of producing high-value plant prenylchalcones using heterologous systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 52 publications
2
97
0
Order By: Relevance
“…5 and 6). A previous study demonstrated that CHIL activates the CHS-mediated production of THC 19 , but we showed that it only weakly induces the PKScatalyzed production of polyketides (THC, CTAL, and BNY). Thus, in essence, CHIL is considered to be a rectifier-rather than an activator-of promiscuous CHS catalysis.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…5 and 6). A previous study demonstrated that CHIL activates the CHS-mediated production of THC 19 , but we showed that it only weakly induces the PKScatalyzed production of polyketides (THC, CTAL, and BNY). Thus, in essence, CHIL is considered to be a rectifier-rather than an activator-of promiscuous CHS catalysis.…”
Section: Discussionmentioning
confidence: 50%
“…The cDNAs encoding flavonoid enzymes of snapdragon, torenia, and soybean [i.e., CHS, chalcone reductase (CHR, soybean), CHI, 2-hydroxyisoflavanone dehydratase (HID, soybean), FNSII (snapdragon and torenia), IFS (soybean), flavanone 3-hydroxylase (F3H, snapdragon), and dihydroflavonol 4-reductase (DFR, snapdragon)] were obtained as previously described [8][9][10] . The CHIL cDNAs of snapdragon 32 , torenia 16 , soybean 8,10 , A. thaliana 18 , rice (Oryza sativa, OsCHIL-A and OsCHIL-B) 19 , and morning glory 16 were obtained as described in the listed references.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was tested by analysis of Marchantia plants with knockout mutations of the chil gene (9). CHIL function is unresolved, but mutant studies in Arabidopsis and Ipomoea nil show that it is generally required for efficient function of the early steps of the flavonoid pathway (37,38) and may noncatalytically enhance chalcone formation and downstream conversion (39). The Mpchil lines had reduced content of both flavones and auronidin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of action of CHIL is unclear, and it may have differing activities across land plants, perhaps based on the promotion of activity of different biosynthetic enzymes through protein-protein interaction. In hop (Humulus lupulus), HlCHIL2 enhances the activities of CHS and an aromatic prenyltransferase (HlPT1L) through protein-protein interaction (Ban et al, 2018), and the promotion of flavonol and proanthocyanidin biosynthesis in Arabidopsis is proposed to be through direct interaction of CHIL and CHI (Jiang et al, 2015). In Marchantia, CHIL may interact with CHS or more than one phenylpropanoid pathway enzyme, since the production of both flavones and auronidins in chil mutants is only about 10% of wild-type amounts .…”
Section: The Phenylpropanoid Biosynthetic Pathway In Bryophytesmentioning
confidence: 99%